Letter to the Project Manager of BUCG-ABC JV mentioning single source for the procurement of goods for BRAC University new campus development project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding letter to the Project Manager of BUCG-ABC JV addressing single source for the procurement of goods for BRAC University new campus development project.